Notes to vascular plants in Ukraine I (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Materials and methods: field observations and herbarium collections, microscope technique Nomenclature: Plants of the World Online (POWO) (2022) Results: In this contribution, new data concerning vascular plants in Ukraine are presented. It includes new records and confirmations for the Ukrainian regions regarding 58 species from the genera of Aconitum, Amaranthus, Anthoxanthum, Artemisia, Asparagus, Cardamine, Carex, Celastrus, Cenchrus, Centaurium, Cerastium, Chenopodiastrum, Clema-tis, Crassula, Dactylorhiza, Datura, Dichodon, Dipsacus, Dysphania, Equisetum, Eritrichium, Euphorbia, Fritillaria, Gagea, Gentiana, Gladi-olus, Glycyrrhiza, Gypsophila, Hedera, Helianthus, Hemerocallis, Hera-cleum, Iris, Juglans, Lemna, Lilium, Lunaria, Lysimachia, Mercurialis, Nymphaea, Pentanema, Prunus, Pulsatilla, Sagina, Scolochloa, Sedum, Silene, Solanum, Sorghum, Stipa, Thesium, Tribulus and Vitis. Among them, three species of vascular plants are newly reported from Ukraine: Anthoxanthum aristatum was found from Chernivtsi Region; Eritrichium nanum – from Ivano-Frankivsk Region; Euphorbia serpens – from Autonomous Republic of Crimea, Kherson Region and Odesa City. Some findings concern large areas including several regions, in particular, a new species for the Right Bank of the Dnipro River (Crassula vaillantii) and a new species for the Steppe zone of Ukraine (Pentanema squar-rosum) are also reported here. Most of the new finds are given for administrative regions of Ukraine: six species are given for the first time for Cherkasy and Zakarpattia Regions, four – for Dnipropetrovsk Region, three – for Chernihiv, Kirovohrad and Zaporizhia Regions, two – for Kherson, Khmelnytsk, Vinnytsia and Volhyn regions, one – for Kharkiv, Mykolaiv, Odesa, Zhytomyr Regions and Autonomous Republic of Crimea. New localities or findings of vascular plant species confirmed by recent data from Cherkasy, Dnipropetrovsk, Kherson, Kirovohrad, Kyiv and Odesa, regions are given. The localities of numerous rare species of vascular plants are provided. Among them, it is species included in the Resolution № 4 of the Bern Convention (i.e. Thesium ebracteatum), the Red Data Book of Ukraine (i.e. Dactylorhiza incarnata, Fritillaria ruthenica, Gladiolus imbricatus, Glycyrrhiza glabra, Lilium martagon, Lunaria rediviva, Pulsatilla patens, Stipa pennata, Stipa tirsa) and regionally rare plants.
Keywords: biodiversity, new finds, regions, district, Ukraine.